A prospective survey study on premenstrual syndrome in young and middle aged women with an emphasis on its management - Brahmbhatt, Shruti; Sattigeri, B. M.; Shah, Heena; Kumar, Ashok; Parikh, Devang (International Journal of Research in Medical Sciences, 2017)
Premenstrual syndrome (PMS) is defined as the recurrence of psychological and physical symptoms in the luteal phase, which remit in the follicular phase of the menstrual cycle. Symptoms of which fall in three domains: emotional, physical and behavioural e.g. irritability, anger, headache, fatigue, food cravings etc. The survey study of was conducted among 50 young & 50 middle aged women of S.B.K.S Medical Institute and Research Centre to find the prevalence of premenstrual syndrome with an emphasis on its management. Responses to a feedback questionnaire covering various aspects related PMS were obtained from 50 participants belonging to each group. The participants belonged to different range of literacy. It was found that 42% faced PMS regularly, while 58% occasionally. Of the 100 participants 68% suffered with backache, 64% leg cramps, 62% fatigue, breast tenderness and anger whereas 58% suffered with anxiety and generalized body ache. Of all the sufferers only 34% had received the treatment for PMS. Irrespective of the age PMS is common problem faced by women. With our study we observed that literacy has not mattered in the management of this health problem. Since there are reports stating that the severity of PMS can hamper the daily routine and even lead to suicidal tendency, it is essential that awareness programs need to be conducted to address the importance of managing the issue by pharmacological and non-pharmacological methods.